Fecal Microbiota Transplantation is a Promising Switch Therapy for Patients with Prior Failure of Infliximab in Crohn's Disease - Qianqian Li; Xiao Ding; Xiao Ding; Yujie Liu; Cicilia Marcella; Min Dai; Ting Zhang; Jianling Bai; Liyuan Xiang; Quan Wen; Bota Cui; Bota Cui; et al. (Frontiers Media S.A., 2021)
Background: How to handle patients with anti-tumor necrosis factor (anti-TNF) failure was a common challenge to clinicians in Crohn's disease (CD). The present study is dedicated to clarifying whether fecal microbiota transplantation (FMT) could be a switch therapy for patients with prior failure of infiiximab (IFX) in CD in a long-term observation.Methods: Thirty-six patients with CD who had prior failure of IFX were recruited from January 2013 to December 2019. The "one-hour FMT protocol" was followed in all patients. All patients received the first course of FMT through gastroscopy or mid-gut transendoscopic enteral tubing. After April 2014, the methodology of FMT was coined as washed microbiota transplantation (WMT), substituting for the manual methods, which is dependent on the automatic microbiota purification system and the washing process. The primary endpoint of this study was the clinical remission at one month and one year after FMT. The secondary endpoint was the safety of FMT in the short and long term, and clinical factors as predictors for long-term efficacy of FMT. Clinical factors as independent predictors of efficacy from FMT were isolated using univariable and multivariable logistic regression analysis.Results: There was no significant difference in the rates of clinical response and remission between IFX treatment stage and FMT treatment stage (at one month, three months and six months after administration) (p > 0.05). Compared with those of 19 patients who achieved clinical remission at one month after FMT, the rates of clinical relapse were significantly higher in 18 patients who achieved clinical remission at one month after IFX [log-rank test p = 0.0009 HR = 3.081 (95% CI 1.43-6.639)]. Multivariate analysis revealed that the gender of donor (95% CI: 0.001-0.72; p = 0.031) was an independent predictor of efficacy at one year after FMT. No serious adverse events (AEs) associated with FMT were observed during and after FMT. The rate of AEs was significantly lower in group FMT than that in group IFX (p = 0.002).Conclusion: The present findings first time provided the evidence for clinicians to consider FMT into practice as an alternative switch therapy for patients with prior loss of response or intolerance to IFX in CD.Clinical Trial Registration:https://clinicaltrials.gov, identifier NCT01793831